Which species to conserve: evaluating children’s species-based conservation priorities - Shapiro, H. G.; Erickson, K. A.; Peterson, M. Nils; Frew, K. N.; Stevenson, K. T.; Langerhans, R. B. (Biodiversity and Conservation, 2016)
We currently have a meager understanding of the species attributes viewed as important for conservation by children, despite the fact that arguments for biodiversity conservation often hinge on the bequest value of species. We conducted a study of children between the ages of 4 and 14 (N = 183) on Andros Island, The Bahamas to determine how they prioritized wildlife species for conservation based on five attributes: endemism, use for hunting and fishing, rapid decline in population size, visibility around their home, and ecological significance. Children tended to rank ecological significance as the most important attribute for prioritizing wildlife for protection, followed closely by endemism, with other attributes being less important and not significantly different from one another. However, participants in a local environmental education program (N = 67) placed greater prioritization to species experiencing rapid population declines. We also found that boys prioritized use for hunting and fishing as more important for conservation than girls, older children placed greater importance on species with declining numbers and less importance on visibility of animals around their house, and children who had previously fished placed greater importance on endemism. These findings help elucidate how children value biodiversity, and suggest children’s conservation priorities may align relatively well with those of conservation biologists, especially after exposure to environmental education. We suggest that better understanding how children prioritize wildlife attributes for conservation can lead to more informed biodiversity conservation decisions and more effective policy implementation, as the perspectives of children can help bridge the gap between public opinion and scientific opinion.